2016
DOI: 10.1371/journal.pone.0166123
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Pomegranate Peel Extract after Chronic Infusion with Amyloid-β Peptide in Mice

Abstract: Alzheimer’s disease is a chronic and degenerative condition that had no treatment until recently. The current therapeutic strategies reduce progression of the disease but are expensive and commonly cause side effects that are uncomfortable for treated patients. Functional foods to prevent and/or treat many conditions, including neurodegenerative diseases, represent a promising field of study currently gaining attention. To this end, here we demonstrate the effects of pomegranate (Punica granatum) peel extract … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 70 publications
(90 reference statements)
2
47
0
Order By: Relevance
“…On the other way, animals that were infused only with Aβ and submitted to the weekly attention training presented evident and significant improvements in memory, which were not observed with animals infused with Aβ + MLA or only MLA. As we have shown before, the chronic infusion of Aβ during 4-5 weeks promote memory loss in mice and rats with deposition of Aβ senile plaques Morzelle et al, 2016;Viel et al, 2012).…”
Section: Discussionsupporting
confidence: 61%
“…On the other way, animals that were infused only with Aβ and submitted to the weekly attention training presented evident and significant improvements in memory, which were not observed with animals infused with Aβ + MLA or only MLA. As we have shown before, the chronic infusion of Aβ during 4-5 weeks promote memory loss in mice and rats with deposition of Aβ senile plaques Morzelle et al, 2016;Viel et al, 2012).…”
Section: Discussionsupporting
confidence: 61%
“…In another study, Morzelle et al evaluated the antiinflammatory effects of PPE following chronic brain infusion of Aβ in mice. They found that PPE (800 mg/kg/day) notably attenuated the levels of amyloid plaque density, acetylcholinesterase activity, lipid peroxidation, and TNF‐α (Morzelle et al, ). Hydroethanolic (50% v/v) extract of pomegranate peel contains a large amount of PU, PL, and EA, which can provide synergistic effects using together.…”
Section: Resultsmentioning
confidence: 99%
“…Sinapic acid is known to exhibit anticancerous, antiglycemic, and neuro‐protective activities that have the potential to attenuate various chemically induced toxicities . Ellagic acid is known for neuro‐protective effects and has been shown to be beneficial in the treatment of Parkinson's disease . Antioxidant activity (AOX) in pomegranate juice ranged from 7.53 to 14.27 mmol L −1 (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Among these, punicalagin, anthocyanins, and ellagic acid are some of the most important compounds responsible for the anti‐inflammatory activity and antimicrobial activity in pomegranate juice. Epidemiological studies have demonstrated beneficial effects of pomegranate‐juice consumption in reducing the risk of cardiovascular disease, diabetes, and neuro‐degeneration …”
Section: Introductionmentioning
confidence: 99%